Parental Responsibility and the Morality of Selective Abortion - Vehmas, Simo (Ethical theory and moral practice, 2002)
It is now a common opinion in Western countries that a child's impairment would probably place an unexpected burden on her parents, a burden that the parents have not committed themselves to dealing with. Therefore, selective abortion is in general a morally justified option for the parents. I argue that this view is based on biased information about the quality of life of individuals with impairments and their families. Also, a conscious decision to procreate should bring about conscious assent to assuming obligations as a parent. This implies a duty of caring for any kind of child. Consequently, if the child's condition is not such that it would make its life not worth living, and if the parents live in an environment where they are able to provide their child and themselves an adequate well-being, they do not have a morally sufficient reason to terminate the pregnancy on the grounds of fetal abnormality.